Rendering reality (2014) - Colorado State University. Department of Design and Merchandising, producer (Colorado State University. Libraries, 2014)
The annual CSU Fashion Show 2014 Rendering Reality will present 25 different collections designed by seniors in the apparel design and production concentration in the Department of Design and Merchandising at Colorado State University. These collections are the highlight of the designers' academic careers, as each piece is designed, constructed, and styled by the students. Design students selected a target market, product category and price zone for their collections. The pieces shown on the runway are unique to the designer, who has drawn the designs, made the patterns, constructed the garment and chosen the fabric. Another unique aspect of the show is the incorporation of decommissioned parachutes into designs. Aspen Pointe, a nonprofit veteran rehabilitation center in Colorado Springs, has donated the parachutes to be utilized in the creation of 14 garments to be displayed.
Modern Visionary: Verretta Anderson, Valerie Grauman, Katie Brutche, Brittany Bates, Brenda Valdez, Tatum Burnett, Melanie Cho.
Endless Adventurer: Andrea Atkins, Lauren Kemp, Brianna Lopez, Cory Hibbard, Phillip Miller, Averie Floyd.
Day Dreamer: Michelle Rushton, Meg Loughman, Geri Nichols-Park, Grace Wexler, Julia Simons.
Midnight Romantic: Brittany Hughes, Taylor Edwards, Kelsay Blair, Janae Philips, Sydni Heldman, Tyler Klene, Joel Lobo.
Keywords: Fashion shows